toner

By incorporating a crystalline and amorphous resin matrix domain structure and silicon-containing fine particles, the toner achieves improved low-temperature fixing and embossing transfer properties, addressing the challenges of charge diffusion and electrostatic adhesion.

JP7654476B2Active Publication Date: 2025-04-01CANON KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021098006
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-11
Publication Date
2025-04-01
Estimated Expiration
2041-06-11

AI Technical Summary

Technical Problem

Existing toners face challenges in achieving excellent low-temperature fixing and embossing transfer properties, with issues related to charge diffusion, electrostatic adhesion, and image density differences on embossed paper.

Method used

The development of toner particles with a specific matrix domain structure composed of a crystalline resin and an amorphous resin, where the crystalline resin occupies 35% to 70% of the total area, and the presence of silicon-containing fine particles on the toner surface, which are characterized by a specific Si-NMR measurement ratio.

Benefits of technology

This solution enables toners to achieve excellent low-temperature fixing properties while maintaining good embossing transfer performance, reducing electrostatic adhesion, and ensuring uniform image density on embossed paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654476000001
    Figure 0007654476000001
  • Figure 0007654476000002
    Figure 0007654476000002
  • Figure 0007654476000003
    Figure 0007654476000003
Patent Text Reader

Abstract

To provide a toner that exhibits excellent low temperature fixability and embossing transferability.SOLUTION: A toner has a toner particle that contains a binder resin having a first resin and a second resin, and fine particles on a surface of the toner particle. The toner has, in its cross section, a matrix-domain structure composed of a matrix including a first crystalline resin and domains including a second amorphous resin, and the ratio of the first resin occupied in the total area is 35 area% or more and 70 area% or less. The first resin has a first long-chain (meth)acrylic monomer unit represented by the different formula. The ratio of the first monomer unit is 40.0-80.0 mass% based on the total mass of all monomer units in the crystalline resin. The fine particles are silicon-containing fine particles. In a chart obtained from 29Si-NMR measurement, when A is the total peak area derived from the silicon-containing fine particles, and B is the area derived from Si-OH, the following formula (2) is satisfied. (2) B / A≥1.0%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner used in electrophotography, electrostatic recording, electrostatic printing, toner jet methods, and the like. [Background technology]

[0002] In recent years, as full-color electrophotographic copiers have become more widespread, there has been a demand for additional performance improvements, such as energy saving performance, shorter recovery time from sleep mode, and compatibility with a wide variety of media, in addition to higher speed and higher image quality. Specifically, as a toner that meets the demand for energy saving, a toner that can be fixed at a lower temperature and has excellent low-temperature fixability is required in order to reduce power consumption in the fixing process. The toner described in Patent Document 1 uses a crystalline vinyl resin having sharp melting properties as the main binder, and therefore has excellent low-temperature fixing properties. Moreover, the toners described in Patent Documents 2 and 3 have a matrix domain structure, and since a crystalline resin having sharp melting properties forms the matrix, excellent low-temperature fixability is possible. On the other hand, embossed paper, one of the many types of media, has an uneven surface, which makes it difficult for the toner to be transferred to the recesses during the transfer process, and this makes it easy for image density differences to occur between the recesses and the protrusions. Therefore, there is a demand for a toner with excellent emboss transferability that does not cause image density differences even on embossed paper. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-130243 A [Patent Document 2] JP 2014-59489 A [Patent Document 3] JP 2014-142632 A Summary of the Invention [Problem to be solved by the invention]

[0004] The toner described in Patent Document 1 uses a crystalline resin with high molecular mobility, which causes charge diffusion and leakage to members such as the drum and intermediate transfer belt (ITB), resulting in a low charge amount for each toner particle. As a result, the electric field driving force becomes small, and the emboss transferability, which has been in demand in recent years, may be poor. In addition, the toners described in Patent Documents 2 and 3 have a toner surface composed of different materials, crystalline resin and amorphous resin, so that electric charges are trapped at the interface, leading to insufficient charge diffusion and a high charge amount at the contact surface. As a result, the electrostatic adhesion to the above-mentioned members increases, and the emboss transferability, which has been required in recent years, may be poor. The present invention has been made in consideration of the above problems, and provides a toner that exhibits excellent low-temperature fixing property and also excellent emboss transferability. [Means for solving the problem]

[0005] The present invention relates to toner particles containing a binder resin having a first resin and a second resin, and a toner having fine particles on the surface of the toner particles, the first resin is a crystalline resin and the second resin is an amorphous resin; a cross section of the toner observed by a transmission electron microscope has a matrix domain structure composed of a matrix containing the first resin and a domain containing the second resin, and the first resin occupies 35 area % or more and 70 area % or less of a total area of ​​the matrix and the domain; The first resin has a first monomer unit represented by the following formula (1):

[0006] [ka] [In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1represents an alkyl group having 18 to 36 carbon atoms.] a ratio of the first monomer unit to the total mass of all monomer units of the crystalline resin is 40.0% by mass or more and 80.0% by mass or less; The microparticles are silicon-containing microparticles, 29 The toner is characterized in that, in a chart obtained by Si-NMR measurement, when the total peak area derived from the silicon-containing fine particles is A and the area derived from Si-OH is B, the following formula (2) is satisfied: B / A≧1.0% (2) Effect of the Invention

[0007] According to the present invention, a toner having excellent low-temperature fixing property and emboss transferability can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] In the present invention, the expressions "xx or more and xx or less" and "xx to xx" expressing a numerical range mean a numerical range including the lower and upper limit endpoints, unless otherwise specified.

[0009] In the present invention, the (meth)acrylic acid ester means an acrylic acid ester and / or a methacrylic acid ester.

[0010] In the present invention, the term "monomer unit" refers to one section of carbon-carbon bonds in the main chain of a polymer formed by polymerization of a vinyl monomer. The vinyl monomer can be represented by the following formula (Z).

[0011] [ka] [In formula (Z), R Z1 represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group), R Z2 represents an optional substituent.

[0012] In the present invention, the crystalline resin refers to a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement.

[0013] Hereinafter, an embodiment of the present invention will be described in detail.

[0014] The present invention relates to toner particles containing a binder resin having a first resin and a second resin, and a toner having fine particles on the surface of the toner particles, the first resin is a crystalline resin and the second resin is an amorphous resin; a cross section of the toner observed by a transmission electron microscope has a matrix domain structure composed of a matrix containing the first resin and a domain containing the second resin, and the first resin occupies 35 area % or more and 70 area % or less of a total area of ​​the matrix and the domain; The first resin has a first monomer unit represented by the following formula (1):

[0015] [ka] [In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms.]

[0016] a ratio of the first monomer unit to the total mass of all monomer units of the crystalline resin is 40.0% by mass or more and 80.0% by mass or less; The microparticles are silicon-containing microparticles, 29 In a chart obtained by Si-NMR measurement, when the total peak area derived from the silicon-containing fine particles is A and the area derived from Si-OH is B, the toner is characterized by satisfying the following formula (2): B / A≧1.0% (2)

[0017] According to the toner of the present invention, it is possible to provide a toner that has both low-temperature fixability and emboss transferability.

[0018] As a result of extensive research, the inventors have found that the above problems can be solved by controlling the matrix domain structure of the crystalline resin and amorphous resin of the toner particles, the area occupied by the crystalline resin, the monomer unit and its amount used in the crystalline resin, and the Si-OH amount of the fine particles on the surface of the toner particles within specific ranges, and have arrived at the present invention.

[0019] The present inventors speculate that the reason for solving the above problem is as follows.

[0020] The transferability of toner is determined by the magnitude relationship between the electric field driving force generated by the electric field and the adhesive force with members such as drums and intermediate transfer belts (ITBs). When the electric field driving force exceeds the adhesive force, the toner can be transferred. The reason why the embossing transferability is poor is that when the gap with the member, such as the recesses of embossed paper, is large, the electric field driving force is small accordingly, and the toner transferability is poor. In addition, while the electric field driving force is largely dependent on the charge amount of each toner particle, the adhesive force is largely dependent on the charge amount of the contact surface with the member, i.e., the uniformity of the charge. Therefore, blindly increasing the charge amount of the toner in order to increase the electric field driving force will not lead to improved embossing transferability, as the adhesive force will also increase at the same time.

[0021] The inventors have discovered that by having a matrix-domain structure consisting of a matrix containing a crystalline resin and a domain containing an amorphous resin, and by controlling the electrostatic charge of the crystalline resin and external additives, it is possible to obtain an excellent low-temperature fixing property, a reduced adhesion force while maintaining an electric field driving force, and excellent emboss transferability.

[0022] In the present invention, it is necessary that the composition has a matrix-domain structure composed of a matrix containing a crystalline resin and a domain containing an amorphous resin, and that the area ratio of the matrix containing the first resin to the total area of ​​the matrix and domain combined is 35 area % or more and 70 area % or less.

[0023] The first resin has a first monomer unit represented by the following formula (1):

[0024] [ka] [In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms.] The proportion of the first monomer unit must be 40.0% by mass or more and 80.0% by mass or less based on the total mass of all monomer units in the crystalline resin.

[0025] Further, in the present invention, the fine particles present on the surface of the toner particles are silicon-containing fine particles, 29 In a chart obtained by Si-NMR measurement, when the total peak area derived from the silicon-containing fine particles is A and the area derived from Si-OH is B, it is necessary that B / A is 1.0% or more.

[0026] By satisfying these requirements, the charging ability of the crystalline resin and the fine particles present on the toner surface become similar, and uniform charging can be achieved, thereby reducing the electrostatic adhesion to the above-mentioned members. Meanwhile, the charge amount per toner particle can be maintained because the charge is trapped at the interface between the crystalline resin and the amorphous resin present inside the toner particle, so that the electric field driving force can be maintained. As a result, a toner was obtained that has excellent low-temperature fixing properties, can reduce the electrostatic adhesion to the above-mentioned members while maintaining the electric field driving force, and has excellent emboss transfer properties.

[0027] Next, each configuration according to the present invention will be described in detail.

[0028] <Matrix domain structure> Of the total area of ​​the matrix and domains on the cross section of the toner, the area ratio of the matrix containing the first resin, which is a crystalline resin, is 35% to 70%, preferably 40% to 60%. When the area ratio of the matrix satisfies the above range, the balance between the uniform charging of the toner surface by the crystalline resin and the fine particles and the charge trapping by the interface between the crystalline resin and the amorphous resin is good, improving the emboss transferability. The above area ratio can be controlled by the ratio of the crystalline resin forming the matrix to the amorphous resin forming the domain.

[0029] The specific methods for observing the cross section of the toner and the matrix domain structure will be described later.

[0030] <First Resin> The first monomer unit represented by the above formula (1) contained in the first resin as a binder resin is derived from a first polymerizable monomer which is at least one selected from the group consisting of (meth)acrylic acid esters having an alkyl group having a carbon number of 18 to 36. When the first resin has the first monomer unit represented by the above formula (1), the charging ability becomes similar to that of the fine particles used, and the emboss transferability becomes good.

[0031] Examples of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms include (meth)acrylic acid esters having a straight-chain alkyl group having 18 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, octacosa (meth)acrylate, myricyl (meth)acrylate, dotriacontane (meth)acrylate, etc.] and (meth)acrylic acid esters having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.].

[0032] Among these, from the viewpoint of low temperature fixability, it is preferably at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group with 18 to 36 carbon atoms. More preferably, it is at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group with 18 to 30 carbon atoms. Even more preferably, it is at least one selected from the group consisting of linear behenyl (meth)acrylate. The polymerizable monomer derived from the first monomer unit represented by the above formula (1) may be used alone or in combination of two or more kinds.

[0033] The content of the first monomer unit in the first resin is 40.0% by mass or more and 80.0% by mass or less, preferably 50.0% by mass or more and 70.0% by mass or less, based on the total mass of all monomer units of the crystalline resin. When the content of the first monomer unit in the first resin satisfies the above range, the charging ability becomes closer to that of the fine particles used, and the emboss transferability becomes good.

[0034] When the crystalline resin has two or more monomer units derived from (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms, the content of the first monomer unit represents the total mass ratio thereof.

[0035] SP value of the first monomer unit (J / cm 3 ) 0.5 is SP1, SP1 is preferably less than 20.00, more preferably 19.00 or less, and even more preferably 18.40 or less. The lower limit is not particularly limited, but is preferably 17.00 or more.

[0036] Here, the SP value is an abbreviation for soluble parameter, and is a value that serves as an index of solubility. The calculation method will be described later.

[0037] In the present invention, the unit of the SP value is (J / cm 3 ) 0.5However, 1 (cal / cm 3 ) 0.5 =0.4888×(J / cm 3 ) 0.5 by (cal / cm 3 ) 0.5 can be converted to units of

[0038] The first resin preferably has a second monomer unit different from the first monomer unit in the first resin. The SP value of the second monomer unit is expressed as SP2 (J / cm 3 ) 0.5 When this is set, it is preferable to satisfy the following relational formula (5), and it is more preferable to satisfy the following relational formula (5)'. 21.00(J / cm 3 ) 0.5 ≦SP2 (5) 25.00(J / cm 3 ) 0.5 ≦SP2 (5)'

[0039] The first monomer unit is incorporated into a polymer, and the first monomer units aggregate with each other to form domains, thereby exhibiting crystallinity. In general, when other monomer units are incorporated, crystallization is easily inhibited, making it difficult for the polymer to exhibit crystallinity.

[0040] This tendency becomes more pronounced when the first monomer unit and the other monomer units are randomly bonded in one molecule of the polymer.

[0041] On the other hand, when SP1 and SP2 are within the ranges described above, it is believed that the first monomer unit and the second monomer unit in the crystalline resin can form a clear phase-separated state without being miscible with each other, and it is believed that the melting point can be easily maintained without reducing crystallinity.

[0042] Specific examples of the second polymerizable monomer that forms the second monomer unit include the following polymerizable monomers. Preferably, a polymerizable monomer that can form a monomer unit represented by the following formula (6) or (7) is used.

[0043] Monomers having a nitrile group; for example, acrylonitrile, methacrylonitrile, etc.

[0044] Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like.

[0045] Monomers having an amide group; for example, acrylamide, monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms (acrylic acid, methacrylic acid, etc.) having an ethylenically unsaturated bond by a known method.

[0046] Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (normal butylamine, t-butylamine, propylamine, isopropylamine, etc.), secondary amine (di-normal ethylamine, di-normal propylamine, di-normal butylamine, etc.), aniline, cycloxylamine, etc.] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method, etc.

[0047] Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate.

[0048] [ka] (In formula (6), X represents a single bond or an alkylene group having 1 to 6 carbon atoms, R 3 teeth, Nitrile group (-C≡N), amide group (-C(=O)NHR 20 (R 20 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. Hydroxy group, -COOR 31 (R 31 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms), Urea group (-NH-C(=O)-N(R 33 )2(R 33 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; -COO(CH2)2NHCOOR 34 (R 34 represents an alkyl group having 1 to 4 carbon atoms, or -COO(CH2)2-NH-C(=O)-N(R 35 )2(R 35 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. represents R 4 represents a hydrogen atom or a methyl group.

[0049] [ka] (In formula (7), R 5 represents an alkyl group having 1 to 4 carbon atoms, R 6 represents a hydrogen atom or a methyl group.

[0050] Among them, it is preferable to use a monomer having a nitrile group, an amide group, a hydroxy group, or a urea group. More preferably, it is a monomer having at least one functional group selected from the group consisting of a nitrile group, an amide group, a hydroxy group, and a urea group, and an ethylenically unsaturated bond. Acrylonitrile and methacrylonitrile are particularly preferable.

[0051] Also preferably used as the second monomer unit are vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, and vinyl octylate. Among these, vinyl esters are preferred from the viewpoint of low-temperature fixability because they are non-conjugated monomers and therefore tend to maintain a suitable reactivity with the first polymerizable monomer and tend to increase the crystallinity of the polymer.

[0052] The proportion of the second monomer unit in the first resin is preferably 5.0% by mass or more and 40.0% by mass or less, and more preferably 10.0% by mass or more and 30.0% by mass or less.

[0053] The copolymer may contain a third monomer unit derived from a third polymerizable monomer not included in the range of the above formula (5) (i.e., different from the first polymerizable monomer and the second polymerizable monomer) as long as the mass ratio of the first monomer unit and the second monomer unit described above is not impaired.

[0054] As the third polymerizable monomer, among the monomers exemplified as the second polymerizable monomer, a monomer not satisfying the above formula (5) can be used.

[0055] For example, the following monomers can also be used:

[0056] Styrene, o-methylstyrene and other styrene and derivatives thereof, (meth)acrylic acid esters such as methyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate. Among these, the third polymerizable monomer is preferably styrene from the viewpoint of charge diffusion.

[0057] The proportion of the third monomer unit in the first resin is preferably 5.0% by mass or more and 50.0% by mass or less, and more preferably 10.0% by mass or more and 30.0% by mass or less.

[0058] <Fine particles> The microparticles are silicon-containing microparticles, 29 In Si-NMR, peaks are detected in different shift regions depending on the structure of the functional group that bonds to the Si of the constituent compounds of the silicon polymer. The structure that bonds to the Si can be identified by identifying the position of each peak using a standard sample. The abundance ratio of each constituent compound can also be calculated from the obtained peak area. The peak area ratios of the Q unit (tetrafunctional silane) structure, T unit (trifunctional silane) structure, D unit (difunctional silane) structure, and M unit (monofunctional silane) structure that make up the fine particles can be calculated.

[0059] In the present invention, when the total peak area derived from silicon-containing fine particles is A and the area derived from Si-OH is B, B / A must be 1.0% or more. Methods for controlling B / A include the type and amount of monomer used in the fine particles, the temperature and time during the condensation reaction, and the pH of the solution. By reducing the amount of tetrafunctional silane used, B / A can be increased. Details of the method for measuring B / A will be described later.

[0060] The method for producing silicon-containing microparticles is not particularly limited, and for example, a silane compound is dropped into water, hydrolyzed and condensed by a catalyst, and the resulting suspension is filtered and dried. The particle size can be controlled by the type of catalyst, the compounding ratio, the reaction start temperature, the dropping time, etc. As the catalyst, acid catalysts include hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, etc., and basic catalysts include ammonia water, sodium hydroxide, potassium hydroxide, etc., but are not limited thereto.

[0061] The number-based average primary particle diameter of the silicon-containing fine particles is preferably 20 nm or more and 300 nm or less, and more preferably 50 nm or more and 150 nm or less.

[0062] Tetrafunctional silanes include tetramethoxysilane, tetraethoxysilane, tetraisocyanate silane, and the like.

[0063] Examples of trifunctional silanes include methyltrimethoxysilane, methyltriethoxysilane, methyldiethoxymethoxysilane, methylethoxydimethoxysilane, methyltrichlorosilane, methylmethoxydichlorosilane, methylethoxydichlorosilane, methyldimethoxychlorosilane, methylmethoxyethoxychlorosilane, methyldiethoxychlorosilane, methyltriacetoxysilane, methyldiacetoxymethoxysilane, methyldiacetoxyethoxysilane, methylacetoxydimethoxysilane, methylacetoxymethoxyethoxysilane, methylacetoxydiethoxysilane, methyltrihydroxysilane, methylmethoxydihydroxysilane, methylethoxydihydroxysilane, methyldimethoxyhydroxysilane, methylethoxymethoxyhydroxysilane, methyldiethoxyhydrosilane, and the like. Examples of the silane include silane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrichlorosilane, ethyltriacetoxysilane, ethyltrihydroxysilane, propyltrimethoxysilane, propyltriethoxysilane, propyltrichlorosilane, propyltriacetoxysilane, propyltrihydroxysilane, butyltrimethoxysilane, butyltriethoxysilane, butyltrichlorosilane, butyltriacetoxysilane, butyltrihydroxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, hexyltrichlorosilane, hexyltriacetoxysilane, hexyltrihydroxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltrichlorosilane, phenyltriacetoxysilane, and phenyltrihydroxysilane.

[0064] Examples of bifunctional silanes include di-tert-butyldichlorosilane, di-tert-butyldimethoxysilane, di-tert-butyldiethoxysilane, dibutyldichlorosilane, dibutyldimethoxysilane, dibutyldiethoxysilane, dichlorodecylmethylsilane, dimethoxydecylmethylsilane, diethoxydecylmethylsilane, dichlorodimethylsilane, dimethoxydimethylsilane, diethoxydimethylsilane, and diethyldimethoxysilane.

[0065] Examples of monofunctional silanes include t-butyldimethylchlorosilane, t-butyldimethylmethoxysilane, t-butyldimethylethoxysilane, t-butyldiphenylchlorosilane, t-butyldiphenylmethoxysilane, t-butyldiphenylethoxysilane, chlorodimethylphenylsilane, methoxydimethylphenylsilane, ethoxydimethylphenylsilane, chlorotrimethylsilane, methoxytrimethylsilane, ethoxytrimethylsilane, triethylmethoxysilane, triethylethoxysilane, tripropylmethoxysilane, tributylmethoxysilane, tripentylmethoxysilane, triphenylchlorosilane, triphenylmethoxysilane, triphenylethoxysilane, and the like.

[0066] The surfaces of the fine particles are preferably treated with a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, but is preferably an organosilicon compound.

[0067] Examples of the hydrophobic treatment agent include alkylsilazane compounds such as hexamethyldisilazane, alkylalkoxysilane compounds such as diethyldiethoxysilane, trimethylmethoxysilane, methyltrimethoxysilane, and butyltrimethoxysilane, fluoroalkylsilane compounds such as trifluoropropyltrimethoxysilane, chlorosilane compounds such as dimethyldichlorosilane and trimethylchlorosilane, siloxane compounds such as octamethylcyclotetrasiloxane, silicone oils, and silicone varnishes.

[0068] The fine particles present on the toner surface are silicon-containing fine particles, 29 In the chart obtained by Si-NMR measurement, the total peak area derived from the particles is A, Si-R 2 (R 2When the area derived from the alkyl group (represents an alkyl group) is defined as C, C / A is preferably 20.0% or more and 45.0% or less. It is more preferably 26.0% or more and 45.0% or less, and even more preferably 30.0% or more and 35.0% or less. When C / A is within the above range, the relationship with the amount of the alkyl group of the first monomer unit in the crystalline resin described above becomes optimal, the charging ability becomes closer, and the embossing transferability becomes good. Methods for controlling C / A include the type and amount of monomer used for the fine particles, the temperature and time during the condensation reaction, and the pH of the solution. C / A can be increased by increasing the amount of bifunctional silane used. Details of the method for measuring C / A will be described later.

[0069] The content of the silicon-containing fine particles is preferably 0.1 parts by mass or more and 20.0 parts by mass or less, and more preferably 3.0 parts by mass or more and 10.0 parts by mass or less, based on 100 parts by mass of the toner particles.

[0070] <Preferred embodiment of domain portion of matrix domain> In the cross-sectional observation of the toner particles, the number average diameter of the circle-equivalent diameter of the domain part containing the second resin described below is preferably 20 nm or more and 500 nm or less, more preferably 100 nm or more and 300 nm or less. When the number average diameter of the circle-equivalent diameter of the domain part satisfies the above range, the dispersibility of the domain in the toner is improved, the trapping of the charge at the interface between the crystalline resin and the amorphous resin is promoted, and the emboss transferability is improved. The method for controlling the number average diameter of the circle-equivalent diameter of the domain part includes the relationship between the SP value of the resin of the matrix part and the domain part, the kneading temperature and the screw rotation speed in the melt kneading process, and the stirring rotation speed in the fusion process. When the SP values ​​of the resins of the matrix part and the domain part are close to each other, the compatibility between the matrix part and the domain part is increased, and the number average diameter of the circle-equivalent diameter of the domain part is reduced. In addition, when the screw rotation speed or the stirring rotation speed is increased, the shear force on the resin is increased, and the number average diameter of the circle-equivalent diameter of the domain part is reduced.

[0071] In observing the cross section of a toner particle, it is preferable that the area of ​​the domain in the region within 10% of the distance between the contour and the center of gravity of the cross section from the contour of the cross section of the toner particle is 10% or more and 30% or less of the total area occupied by the domain. It is more preferable that the area of ​​the domain in the region within 10% of the distance between the contour and the center of gravity of the cross section from the contour satisfies the above range, and while maintaining uniform charging by the crystalline resin and fine particles present on the surface, an interface between the crystalline resin and the amorphous resin exists near the surface, charge trapping is promoted, and emboss transferability is improved. Examples of a method for controlling the area of ​​the domain in the region within 10% of the distance between the contour and the center of gravity of the cross section from the contour include the presence or absence of a core-shell structure, the type and amount of shell agent added, and the stirring rotation speed and time of the fusion process. Since the first monomer unit described above is highly hydrophobic, the amorphous resin in the domain portion becomes relatively hydrophilic. Since the fusion step is carried out in water, by lengthening the fusion step time and increasing the stirring rotation speed, the hydrophilic amorphous resin can be positioned near the surface.

[0072] The method for measuring the number-average equivalent circle diameter of the domain and the area of ​​the domain in a region within 10% of the distance from the contour to the center of gravity of the cross section will be described later in detail.

[0073] <Second Resin> The binder resin contains a second resin, and the second resin is an amorphous resin.

[0074] As the amorphous resin, from the viewpoint of trapping electric charges, a polyester resin, a styrene-acrylic resin, or a hybrid resin thereof is preferable, and a styrene-acrylic resin is more preferable.

[0075] As the styrene-acrylic resin, a styrene-acrylic resin that is usually used in a toner can be suitably used.

[0076] Examples of styrene monomers include styrene, α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, p-methoxystyrene, and p-phenylstyrene. These styrene monomers can be used alone or in combination.

[0077] Examples of the (meth)acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-amyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, dimethyl phosphate ethyl (meth)acrylate, diethyl phosphate ethyl (meth)acrylate, dibutyl phosphate ethyl (meth)acrylate, and 2-benzoyloxyethyl (meth)acrylate, (meth)acrylonitrile, 2-hydroxyethyl (meth)acrylate, (meth)acrylic acid, and maleic acid. These (meth)acrylic monomers can be used alone or in combination.

[0078] As the polyester resin, a polyester resin that is usually used in a toner can be suitably used. As a monomer used in the polyester resin, a polyhydric alcohol (a divalent or trivalent or higher alcohol), a polyvalent carboxylic acid (a divalent or trivalent or higher carboxylic acid), an acid anhydride thereof, or a lower alkyl ester thereof can be mentioned.

[0079] The polyhydric alcohols include the following:

[0080] Examples of dihydric alcohols include the following bisphenol derivatives.

[0081] Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane, etc.

[0082] Other polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.

[0083] These polyhydric alcohols can be used alone or in combination.

[0084] Examples of the polyvalent carboxylic acid include the following.

[0085] Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.

[0086] Examples of trivalent or higher carboxylic acids, their acid anhydrides, and their lower alkyl esters include the following.

[0087] 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, acid anhydrides thereof, or lower alkyl esters thereof.

[0088] Among these, 1,2,4-benzenetricarboxylic acid (trimellitic acid) or its derivatives such as an acid anhydride are preferably used because they are inexpensive and the reaction can be easily controlled.

[0089] These polyvalent carboxylic acids can be used alone or in combination.

[0090] <Other resins> The binder resin may contain a resin other than the first resin and the second resin for the purpose of improving pigment dispersibility, etc., to an extent that the effects of the present disclosure are not impaired.

[0091] The resins include the following:

[0092] Polyvinyl chloride, phenolic resin, natural resin modified phenolic resin, natural resin modified maleic acid resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane resin, polyamide resin, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, petroleum-based resin.

[0093] <Wax> The toner particles of the present invention may contain a wax, if necessary. Examples of the wax include the following.

[0094] Hydrocarbon waxes such as microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes whose main component is fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax.

[0095] Further examples include the following: saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and parinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene saturated fatty acid bisamides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N'-dioleyl adipamide, N,N'-dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearyl isophthalamide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxy groups obtained by hydrogenation of vegetable oils and fats.

[0096] The content of the wax is preferably 2.0 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the binder resin.

[0097] <Coloring agent> The toner particles of the present invention may contain a colorant, if necessary. Examples of the colorant include the following.

[0098] Examples of black colorants include carbon black, and a mixture of a yellow colorant, a magenta colorant, and a cyan colorant toned to black. As the colorant, a pigment may be used alone, but it is more preferable to use a dye and a pigment in combination to improve the clarity of the colorant from the viewpoint of the image quality of a full-color image.

[0099] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.

[0100] Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.

[0101] Pigments for cyan toners include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45; copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton.

[0102] Cyan toner dyes include CI Solvent Blue 70.

[0103] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.

[0104] These colorants can be used alone or in combination, or in the form of a solid solution. The colorant is selected in consideration of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility in toner.

[0105] The content of the colorant is preferably 0.1 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the total amount of the resin components.

[0106] <Charge control agent> The toner particles of the present invention may contain a charge control agent, if necessary. By blending a charge control agent, the charge characteristics can be stabilized and the amount of triboelectric charge can be optimally controlled according to the development system.

[0107] As the charge control agent, known substances can be used, but particularly preferred are metal compounds of aromatic carboxylic acids, which are colorless, can charge the toner quickly, and can stably maintain a constant charge amount.

[0108] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.

[0109] The charge control agent may be added internally or externally to the toner particles. The content of the charge control agent is preferably 0.2 parts by mass to 10.0 parts by mass, more preferably 0.5 parts by mass to 10.0 parts by mass, based on 100 parts by mass of the binder resin.

[0110] <Inorganic fine particles> In addition to the above-mentioned fine particles, the toner may contain other inorganic fine particles as necessary. The inorganic fine particles may be added internally to the toner particles, or may be mixed with the toner particles as an external additive. When added as an external additive, inorganic fine particles such as titanium oxide fine particles and aluminum oxide fine particles are preferred. The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.

[0111] As an external additive to improve fluidity, 2 / g or more 400m 2 In order to simultaneously improve the flowability and stabilize the durability, inorganic fine particles having a specific surface area within the above range may be used in combination.

[0112] The amount of the inorganic fine particles is preferably 0.1 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the toner particles.

[0113] <Developer> The toner of the present invention can be used as a one-component developer, but is more preferably mixed with a magnetic carrier and used as a two-component developer in that stable images can be obtained over a long period of time.

[0114] Examples of magnetic carriers that can be used include generally known magnetic carriers such as iron powder with an oxidized surface, unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, and rare earth elements, alloy particles thereof, oxide particles, magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state.

[0115] When the toner of the present invention is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio in terms of the toner concentration in the two-component developer is preferably 2.0% by mass or more and 15.0% by mass or less, more preferably 4.0% by mass or more and 13.0% by mass or less.

[0116] <Toner manufacturing method> The method for producing the toner of the present invention is not particularly limited, and known methods such as a pulverization method, a suspension polymerization method, a dissolution suspension method, an emulsion aggregation method, and a dispersion polymerization method can be used.

[0117] The procedure for producing the toner by the pulverization method will be described below.

[0118] [Raw material mixing process] In the raw material mixing process, materials constituting the toner particles, such as binder resin, wax, colorant, and other components such as charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include a double cone mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, and a Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.).

[0119] [Melting and kneading process] Next, the mixed materials are melt-kneaded to disperse the wax in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with a two-roller or the like, and cooled with water or the like in a cooling process.

[0120] The state of dispersion of the first resin and the second resin, the number-average diameter of the domains, and the like can be controlled by adjusting the kneading temperature in the melt-kneading step, the number of revolutions of the screw, and the like.

[0121] [Crushing process] The cooled resin composition is then pulverized to a desired particle size in a pulverization process, which involves coarse pulverization using a pulverizer such as a crusher, hammer mill, or feather mill, followed by further pulverization using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.

[0122] [Classification process] Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).

[0123] [External addition process] Furthermore, if necessary, an external additive is added to the surface of the toner particles. As a method for adding an external additive, a method is mentioned in which a predetermined amount of a classified toner and various known external additives are mixed, and stirred and mixed using a mixing device such as a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation) as an external additive machine.

[0124] Next, the production of toner particles by the emulsion aggregation method will be described.

[0125] In the emulsion aggregation method, toner particles are manufactured through a dispersion process in which a fine particle dispersion liquid made of the constituent materials of the toner particles is prepared, an aggregation process in which fine particles made of the constituent materials of the toner particles are aggregated and the particle size is controlled until the particle size becomes the same as that of the toner particles, a fusion process in which the resin contained in the obtained aggregated particles is fused, a subsequent cooling process, a metal removal process in which the obtained toner is filtered and excess polyvalent metal ions are removed, a filtration / washing process in which the toner particles are washed with ion-exchanged water or the like, and a process in which moisture is removed from the washed toner particles and they are dried.

[0126] [Step of preparing a resin particle dispersion (dispersion step)] The resin microparticle dispersion liquid can be prepared by a known method, but is not limited to these methods.The known methods include, for example, emulsion polymerization method, self-emulsification method, phase inversion emulsification method in which resin is emulsified by adding aqueous medium to the resin solution dissolved in organic solvent, and forced emulsification method in which resin is forcedly emulsified by high temperature treatment in aqueous medium without using organic solvent.

[0127] Specifically, the first resin and the second resin are dissolved in an organic solvent capable of dissolving them, and a surfactant or a basic compound is added as necessary. In this case, if the resin is a crystalline resin having a melting point, it may be dissolved by heating to above the melting point. Next, while stirring with a homogenizer or the like, an aqueous medium is slowly added to precipitate the resin fine particles. Thereafter, the solvent is removed by heating or reducing pressure to prepare an aqueous dispersion of the resin fine particles.

[0128] As the organic solvent used to dissolve the resin, any organic solvent that can dissolve the resin can be used, but it is preferable to use an organic solvent that forms a homogeneous phase with water, such as toluene, from the viewpoint of suppressing the generation of coarse powder.

[0129] The surfactant is not particularly limited, and examples thereof include anionic surfactants such as sulfate salts, sulfonates, carboxylates, phosphates, and soaps, cationic surfactants such as amine salts and quaternary ammonium salts, and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. The surfactants may be used alone or in combination of two or more.

[0130] Examples of the basic compound include inorganic bases such as sodium hydroxide and potassium hydroxide, and organic bases such as ammonia, triethylamine, trimethylamine, dimethylaminoethanol, and diethylaminoethanol. The basic compound may be used alone or in combination of two or more kinds.

[0131] The 50% particle size (D50) based on volume distribution of the resin fine particles in the aqueous dispersion of the resin fine particles is preferably about 0.05 μm to 1.00 μm, and more preferably about 0.05 μm to 0.40 μm. By adjusting the 50% particle size (D50) based on volume distribution to the above range, it becomes easy to obtain toner particles with a weight average particle size of 3 μm to 10 μm, which is appropriate for toner particles.

[0132] In addition, the 50% particle size (D50) based on volume distribution can be measured using a dynamic light scattering particle size distribution meter Nanotrac UPA-EX150 (manufactured by Nikkiso).

[0133] [Preparation of colorant particle dispersion] The colorant particle dispersion liquid can be prepared by the following known methods, but is not limited to these methods.

[0134] The colorant, the aqueous medium, and the dispersant can be mixed by a known mixer such as a stirrer, an emulsifier, or a disperser. The dispersant used here can be a known one such as a surfactant or a polymer dispersant.

[0135] Although both the surfactant and the polymer dispersant can be removed in the washing step described below, the surfactant is preferred from the viewpoint of washing efficiency.

[0136] Examples of surfactants include anionic surfactants such as sulfate ester salts, sulfonate salts, phosphate esters, and soap-based surfactants; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols.

[0137] Among these, nonionic surfactants or anionic surfactants are preferred. A nonionic surfactant and an anionic surfactant may be used in combination. The surfactant may be used alone or in combination of two or more. The concentration of the surfactant in the aqueous medium is preferably about 0.5% by mass to 5% by mass.

[0138] The content of the colorant particles in the colorant particle dispersion is not particularly limited, but is preferably 1% by mass to 30% by mass with respect to the total mass of the colorant particle dispersion.

[0139] From the viewpoint of dispersibility of the colorant in the toner particles finally obtained, the dispersed particle size of the colorant particles in the aqueous dispersion of the colorant is preferably 0.50 μm or less in terms of the 50% particle size (D50) based on the volume distribution. For the same reason, it is preferable that the 90% particle size (D90) based on the volume distribution is 2 μm or less. The 50% particle size (D50) based on the volume distribution of the colorant particles dispersed in the aqueous medium may be measured using a dynamic light scattering particle size distribution meter (Nanotrac UPA-EX150: manufactured by Nikkiso).

[0140] Known mixers such as stirrers, emulsifiers, and dispersers used when dispersing a colorant in an aqueous medium include ultrasonic homogenizers, jet mills, pressure homogenizers, colloid mills, ball mills, sand mills, and paint shakers. These may be used alone or in combination.

[0141] [Preparation of wax particle dispersion] The wax particle dispersion can be prepared by the following known methods, but is not limited to these methods.

[0142] Wax microparticle dispersions can be produced by adding wax to an aqueous medium containing a surfactant, heating it to above the melting point of the wax, dispersing it into particles using a homogenizer with strong shearing capabilities (e.g., M Technique's "Clearmix W Motion") or a pressure-discharge type disperser (e.g., Gaulin Homogenizer) and then cooling it below the melting point.

[0143] The particle size of the dispersed wax particles in the aqueous wax dispersion is preferably about 0.03 μm to 1.0 μm, more preferably 0.10 μm to 0.50 μm, in terms of the 50% particle size (D50) based on volume distribution. It is also preferable that no coarse particles of 1 μm or more exist.

[0144] By having the dispersed particle size of the wax microparticle dispersion within the above range, it becomes possible to have the wax finely dispersed in the toner particles, which maximizes the exudation effect during fixing and makes it possible to obtain good separation properties. The 50% particle size (D50) based on the volume distribution of the wax microparticle dispersion dispersed in the aqueous medium can be measured using a dynamic light scattering particle size distribution meter (Nanotrac UPA-EX150: manufactured by Nikkiso).

[0145] [Mixing process] In the mixing step, a mixed liquid is prepared by mixing the first resin particle dispersion liquid, the second resin particle dispersion liquid, and, if necessary, the wax particle dispersion liquid and the colorant particle dispersion liquid, etc. This may be carried out using a known mixing device such as a homogenizer or a mixer.

[0146] [Step of forming aggregate particles (aggregation step)] In the aggregation step, the fine particles contained in the mixed liquid prepared in the mixing step are aggregated to form aggregates of the desired particle size. At this time, an aggregating agent is added and mixed as necessary, and at least one of heating and mechanical power is appropriately applied to form aggregates in which the resin fine particles and, as necessary, the wax fine particles and the colorant fine particles are aggregated. By adjusting the mechanical power, it is possible to control the dispersion state of the first resin and the second resin, the number average diameter of the domains, and the like.

[0147] As the flocculant, a flocculant containing a divalent or higher metal ion may be used as necessary.

[0148] The flocculants containing divalent or higher metal ions have high flocculation power and can achieve the purpose by adding a small amount. These flocculants can also ionically neutralize the ionic surfactants contained in the resin particle dispersion, the wax particle dispersion, and the colorant particle dispersion.

[0149] As a result, due to the effects of salting out and ionic crosslinking, the resin particles, wax particles, and colorant particles tend to aggregate.

[0150] In the aggregation step, after the aggregates are formed, new resin particle dispersion may be added as necessary. By adding new resin particle dispersion and aggregating, a core-shell structure can be realized. The aggregation step is a step of forming aggregates of the toner particle size in an aqueous medium. The weight-average particle diameter of the aggregates produced in the aggregation step is preferably 3 μm to 10 μm. The weight-average particle diameter may be measured using a particle size distribution analyzer (Coulter Multisizer III, manufactured by Coulter) using the Coulter method.

[0151] [Fusion process] In the fusion step, an aggregation terminator may be added to the dispersion containing the aggregates obtained in the aggregation step under stirring in the same manner as in the aggregation step. Examples of the aggregation terminator include a basic compound that shifts the equilibrium of the acidic polar group of the surfactant to the dissociation side and stabilizes the aggregated particles. In addition, examples of the aggregation terminator include a chelating agent that partially dissociates the ionic bridge between the acidic polar group of the surfactant and the metal ion serving as the aggregating agent, and forms a coordinate bond with the metal ion to stabilize the aggregated particles.

[0152] After the dispersion state of the aggregated particles in the dispersion liquid has become stable due to the action of the aggregation terminator, the aggregated particles may be fused by heating to a temperature equal to or higher than the glass transition temperature or melting point of the resin.

[0153] It is also possible to control the number-average diameter of the domains by adjusting the temperature during fusion. The weight-average particle diameter of the obtained toner particles is preferably about 3 μm to 10 μm.

[0154] [Filtration process, washing process, drying process, classification process] Thereafter, a filtration step for filtering out the solid content of the toner particles, and if necessary, a washing step, a drying step, and a classification step for adjusting the particle size are carried out to obtain toner particles.

[0155] The obtained toner particles may be used as a toner as it is. The obtained toner particles may be mixed with inorganic fine particles and, if necessary, other external additives to obtain a toner. The toner particles, inorganic fine particles, and other external additives may be mixed using a mixing device such as a double con mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation).

[0156] The methods for measuring various physical properties are described below.

[0157] <Separation of toner particles and fine particles from toner> The toner particles and fine particles can be separated from the toner by the following method.

[0158] Add 200 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Place 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments, pH 7, consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) in a centrifuge tube to prepare a dispersion. Add 1 g of toner to this dispersion and break up the toner clumps with a spatula or the like.

[0159] The centrifuge tube is shaken for 20 minutes in a shaker (Iwaki Sangyo Co., Ltd. "KM Shaker" (model: V.SX)) at 350 back and forth revolutions per minute. After shaking, the solution is transferred to a glass tube for a swing rotor (50 mL) and centrifuged at 3500 rpm for 30 minutes in a centrifuge. After centrifugation, toner particles are present in the top layer in the glass tube, and fine particles are present in the aqueous solution side in the lower layer. The toner particles in the top layer are collected.

[0160] <Method of separating each material from toner> By utilizing the difference in solubility of each material contained in the toner in a solvent, each material can be separated from the toner. First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble matter (second resin) is separated from the insoluble matter (first resin, wax, colorant, inorganic fine particles, etc.). Second separation: The insoluble matter obtained in the first separation (first resin, wax, colorant, inorganic fine particles, etc.) is dissolved in MEK at 100°C, and the soluble matter (first resin, wax) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated. Third separation: The soluble fraction (first resin, wax) obtained in the second separation is dissolved in chloroform at 23° C., and the soluble fraction (first resin) and the insoluble fraction (wax) are separated.

[0161] (When a third resin is included) First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble matter (second resin, third resin) is separated from the insoluble matter (first resin, wax, colorant, inorganic fine particles, etc.). Second separation: The soluble fraction (second resin, third resin) obtained in the first separation is dissolved in toluene at 23° C., and the soluble fraction (third resin) is separated from the insoluble fraction (second resin). Third separation: The insoluble matter obtained in the first separation (first resin, wax, colorant, inorganic fine particles, etc.) is dissolved in MEK at 100°C, and the soluble matter (first resin, wax) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated. Fourth separation: The soluble fraction (first resin, wax) obtained in the third separation is dissolved in chloroform at 23° C., and the soluble fraction (first resin) and the insoluble fraction (wax) are separated.

[0162] (Measurement of the Contents of the First Resin and the Second Resin in the Binder Resin in the Toner) In each of the separation steps, the masses of the soluble and insoluble components are measured to calculate the contents of the first resin and the second resin in the binder resin in the toner.

[0163] <Method of Identifying Monomer Units Constituting the First, Second, and Third Resins and Measuring Their Content Ratios> The identification and content ratio of the monomer units constituting the first, second and third resins are measured by:1 H-NMR was performed under the following conditions. Measuring device: FT NMR device JNM-EX400 (manufactured by JEOL Ltd.) Measurement frequency: 400MHz Pulse condition: 5.0μs Frequency range: 10500Hz Number of times: 64 Measurement temperature: 30℃ Sample: 50 mg of the measurement sample is placed in a sample tube with an inner diameter of 5 mm, deuterated chloroform (CDCl3) is added as a solvent, and this is dissolved in a constant temperature bath at 40°C to prepare the sample.

[0164] Obtained 1 From the H-NMR chart, a peak that is independent of the peaks that are assigned to the components of the first monomer unit is selected, and the integral value S1 of this peak is calculated.

[0165] Similarly, from the peaks attributable to the components of the second monomer unit, a peak independent of the peaks attributable to the components of the other monomer units is selected, and the integral value S2 of this peak is calculated.

[0166] Furthermore, in the case where a third monomer unit is present, a peak that is independent of the peaks attributable to the components of the third monomer unit is selected from the peaks attributable to the components of the other monomer units, and the integral value S3 of this peak is calculated.

[0167] The content ratio of the first monomer unit is determined using the above integral values ​​S1, S2, and S3 as follows: Here, n1, n2, and n3 are the numbers of hydrogen atoms in the constituent elements to which the peaks of interest for each site belong. Content of first monomer unit (mol%)= {(S1 / n1) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100

[0168] Similarly, the contents of the second monomer unit and the third monomer unit are determined as follows. Content of second monomer unit (mol%)= {(S2 / n2) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100 Content of third monomer unit (mol%)= {(S3 / n3) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100

[0169] In addition, in the first, second and third resins, for example, when a polymerizable monomer that does not contain a hydrogen atom in a component other than a vinyl group is used, 13 Measure nuclei using C-NMR 13 C, and the measurement was performed in single pulse mode. 1 Calculation is performed in the same manner as for H-NMR.

[0170] The mole % can be converted to mass % based on the molecular weight of the monomer unit.

[0171] <Measurement of B / A and C / A of fine particles> solid 29 Specifically, the Si-NMR measurement conditions are as follows: Equipment: JNM-ECX5002 (JEOL RESONANCE) Temperature: room temperature Measurement method: DDMAS method 29Si 45° Sample tube: Zirconia 3.2mmφ Sample: Powdered material filled into test tube Sample rotation speed: 10kHz Relaxation delay: 180s Scan:2000

[0172] The peak area derived from the M unit structure is S1, the peak area derived from the D unit structure is S2, the peak area derived from the T unit structure is S3, and the peak area derived from the Q unit structure is S4, and SA=(S1+S2+S3+S4).

[0173] (Calculation method for B / A) solid 29 From the chart obtained by Si-NMR, the peak area of ​​the unreacted group (Si-OH) in each unit structure at the following positions is calculated. The peak area of ​​the unreacted group (Si-OH) in the Q4 unit structure is S44, the peak area of ​​the unreacted group (Si-OH) in the Q3 unit structure is S43, the peak area of ​​the unreacted group (Si-OH) in the Q2 unit structure is S42, and the peak area of ​​the unreacted group (Si-OH) in the Q1 unit structure is S41.

[0174] The peak area of ​​the unreacted group (Si-OH) in the T3 unit structure is S33, the peak area of ​​the unreacted group (Si-OH) in the T2 unit structure is S32, and the peak area of ​​the unreacted group (Si-OH) in the T1 unit structure is S31.

[0175] The peak area of ​​the unreacted group (Si-OH) in the D2 unit structure is designated as S22, and the peak area of ​​the unreacted group (Si-OH) in the D1 unit structure is designated as S21.

[0176] The peak area of ​​the unreacted group (Si-OH) in the M1 unit structure is designated as S11.

[0177] At this time, the peak area ratio of Si-OH in each unit structure is calculated as follows.

[0178] The peak area ratio of Si-OH assigned to the Q unit structure, QB=(S44 / S4)×0+(S43 / S4)×1 / 4+(S42 / S4)×1 / 2+(S41 / S4)×3 / 4, The peak area ratio of Si-OH attributable to the T unit structure TB=(S33 / S3)×0+(S32 / S3)×1 / 4+(S31 / S3)×1 / 2, The peak area ratio of Si-OH attributable to the D unit structure DB=(S22 / S2)×0+(S21 / S2)×1 / 4, Peak area ratio of Si-OH assigned to M unit structure MB = S11 × 0 Q unit structure Q4: -105ppm~-115ppm Q3: -95ppm~-104ppm Q2:-85ppm~-94ppm Q1:-75ppm~-84ppm T unit structure T3: -60ppm~-70ppm T2: -50ppm~-59ppm T1: -40ppm~-49ppm D unit structure D2: -15ppm~-25ppm D1: -10ppm~14ppm M unit structure M1: -5ppm~-9ppm

[0179] From the above formula, calculate B / A=QB+TB+DB+MB.

[0180] (Calculation method of C / A) solid 29 From the chart obtained by Si-NMR, the (Si-R 2 ) peak area is calculated. 2 represents an alkyl group.

[0181] Q4 unit structure (Si-R 2 ) in the S44 and Q3 unit structures. 2 ) in the S43 and Q2 unit structures (Si-R 2 ) in the S42 and Q1 unit structures (Si-R 2 ) is defined as S41.

[0182] (Si-R 2 ) in the S33 and T2 unit structures. 2 ) in the S32 and T1 unit structures. 2 ) is defined as S31.

[0183] (Si-R 2 ) in the S22 and D1 unit structures (Si-R 2 ) is defined as S21.

[0184] (Si-R 2 ) is defined as S11. In this case, the Si-R peak area in each unit structure is as follows: 2 The peak area ratio is calculated. Si-R assigned to Q unit structure 2 Peak area ratio QC=(S44 / S4)×0+(S43 / S4)×0+(S42 / S4)×0+(S41 / S4)×0 Peak area ratio of Si-R2 attributed to T unit structure TC = (S33 / S3) × 1 / 4 + (S32 / S3) × 1 / 4 + (S31 / S3) × 1 / 4 Peak area ratio DC of Si-R2 attributed to D unit structure = (S22 / S2) × 1 / 2 + (S21 / S2) × 1 / 2 Peak area ratio of Si-R2 attributed to M unit structure MC = S11 × 3 / 4 Q unit structure Q4: -105ppm~-115ppm Q3: -95ppm~-104ppm Q2:-85ppm~-94ppm Q1:-75ppm~-84ppm T unit structure T3: -60ppm~-70ppm T2: -50ppm~-59ppm T1: -40ppm~-49ppm D unit structure D2: -15ppm~-25ppm D1: -10ppm~14ppm M unit structure M1: -5ppm~-9ppm

[0185] From the above formula, calculate C / A=QC+TC+DC+MC.

[0186] <Method for measuring the peak top temperature of endothermic peaks measured by differential scanning calorimetry (DSC) of crystalline resins> The peak top temperature of the endothermic peak measured by differential scanning calorimetry (DSC) of the crystalline resin is measured in accordance with ASTM D3418-82 using a differential scanning calorimeter "Q2000" (manufactured by TA Instruments).

[0187] The melting points of indium and zinc are used for temperature correction of the device detection section, and the heat of fusion of indium is used for heat correction.

[0188] Specifically, about 3 mg of a sample is precisely weighed and placed in an aluminum pan, and measurement is performed under the following conditions using an empty aluminum pan as a reference. Heating rate: 10℃ / min Measurement start temperature: 30℃ End of measurement temperature: 180℃

[0189] Measurements are performed in the measurement range of 30 to 180°C at a heating rate of 10°C / min. The temperature is raised to 180°C once and held for 10 minutes, then cooled to 30°C, and then heated again. During this second heating process, the peak top temperature of the crystalline resin is calculated from the temperature-endothermic curve in the temperature range of 30°C to 80°C.

[0190] The peak top temperature of the endothermic peak of the wax (mold release agent) is also measured in the same manner as above.

[0191] <Observation of toner cross section, observation of matrix domain structure, measurement of number-average equivalent circle diameter of domain, measurement of domain area within 10% of the distance from the contour to the center of gravity of the cross section> (Observation of toner cross section, observation of matrix domain structure) First, a thin slice is prepared as a reference sample for the amount present. The first resin, which is a crystalline resin, is thoroughly dispersed in a visible light curable resin (Aronix LCR Series D800), and then irradiated with short wavelength light to harden it. The obtained hardened material is cut with an ultramicrotome equipped with a diamond knife to prepare a thin slice sample of 250 nm. In the same manner, a thin slice sample is also prepared for the second resin, which is an amorphous resin.

[0192] In addition, the first resin and the second resin are mixed in a ratio of 30 / 70 and 70 / 30 by mass, and melt-kneaded to prepare a kneaded product.

[0193] These are also similarly dispersed in a visible light curable resin, hardened, and then cut out to prepare thin-section samples. Next, the cut-out samples are observed on the cross section of these reference samples using a transmission electron microscope (JEM-2800 electron microscope manufactured by JEOL Ltd.) (TEM-EDX), and element mapping is performed using EDX. The elements to be mapped are carbon, oxygen, and nitrogen. The mapping conditions are as follows: Acceleration voltage: 200 kV Electron beam irradiation size: 1.5 nm Live time limit: 600sec Dead time: 20~30 Mapping resolution: 256×256

[0194] Based on the spectral intensity (average in an area of ​​10 nm square) of each element, calculate (oxygen element intensity / carbon element intensity) and (nitrogen element intensity / carbon element intensity) and create a calibration curve for the mass ratio of the first resin to the second resin. If the monomer unit of the first resin contains nitrogen atoms, the calibration curve of (nitrogen element intensity / carbon element intensity) will be used for future quantification.

[0195] Next, the toner sample is analyzed. After thoroughly dispersing the toner in a visible light curable resin (Aronix LCR Series D800), it is irradiated with short wavelength light and cured. The resulting cured product is cut out using an ultramicrotome equipped with a diamond knife to prepare a 250 nm thin sample. The cut sample is then observed using a transmission electron microscope (JEOL JEM-2800) (TEM-EDX). Cross-sectional images of the toner particles are obtained, and elemental mapping is performed using EDX. The elements to be mapped are carbon, oxygen, and nitrogen.

[0196] The toner particle cross section to be observed is selected as follows. First, the cross-sectional area of ​​the toner particle is obtained from the toner particle cross-sectional image, and the diameter (equivalent circle diameter) of a circle having an area equal to the cross-sectional area is obtained. Only toner particle cross-sectional images in which the absolute value of the difference between this equivalent circle diameter and the weight average particle diameter (D4) of the toner particle is within 1.0 μm are observed. For the domains confirmed in the observed image of the toner particle, (oxygen element intensity / carbon element intensity) and / or (nitrogen element intensity / carbon element intensity) are calculated based on the (average of 10 nm square) spectral intensity of each element, and the ratio of the first resin to the second resin is calculated by comparing with the calibration curve. Domains in which the ratio of the second resin is 80% or more are defined as domains of the present disclosure.

[0197] When the ratio of the toner particle cross section forming a matrix domain structure among the toner particle cross sections is 80% by number or more, the toner particle cross section of the toner to be measured is determined to have a matrix domain structure. The matrix domain structure is a state in which domains, which are discontinuous phases, are dispersed in a matrix, which is a continuous phase. Here, the continuous phase means that, in the toner particle cross section, when 90% or more of the area of ​​the first resin or the area occupied by the second resin exists as one continuous region, the first resin or the second resin is determined to be a continuous phase.

[0198] (Measurement of the number-average diameter of the equivalent circle diameter of the domain) After identifying the domains confirmed by the observed image, the particle size of the domains present on the cross section of the toner particle is obtained by binarization processing. The particle size is the circle-equivalent diameter of the domain. This is measured at 10 points per toner particle, and the arithmetic average of the domain particle sizes of the 10 toner particles is taken as the number-average circle-equivalent diameter of the domain (μm).

[0199] (Measurement of the area of ​​the domain within 10% of the distance from the contour to the center of gravity of the cross section) Meanwhile, the area of ​​the domains is calculated by adding up the areas of all the domains present in one toner particle cross-sectional image to obtain the total area, which is designated as S1. The total area of ​​the domains of 100 toner particles (i.e., S1 + S2... + S100) is calculated, and the arithmetic average value of the 100 particles is designated as the "domain area."

[0200] Regarding the cross-sectional area of ​​the toner particle, the total cross-sectional area of ​​the toner particle (100 toner particles) obtained from the toner cross-sectional images used to calculate the area of ​​the domain is calculated, and the arithmetic average value is regarded as the "total cross-sectional area of ​​the toner particle." In addition, the "total cross-sectional area of ​​the toner particle" - [area of ​​the domain] is regarded as the [area of ​​the matrix]. Then, [area of ​​the matrix] / ([area of ​​the domain] + [area of ​​the matrix]) x 100 is regarded as the area ratio of the matrix to the total area of ​​the matrix and domain combined.

[0201] The area of ​​the domain in the region within 10% of the distance between the contour and the center of gravity of the cross section from the contour is determined using the toner cross section image used to determine the area of ​​the domain. The contour of the toner particle is set along the surface of the toner particle observed in the cross section image. The center of gravity of the toner particle is set to the center of a circle having an area equal to the cross section area of ​​the toner particle observed in the cross section image. A line is drawn from the center of gravity of the toner particle cross section to a point on the contour of the toner particle cross section. On the line, a position that is 10% of the distance from the contour to the center of gravity of the cross section is specified. Then, this operation is performed for one circumference of the contour of the toner particle cross section, and a boundary line of 10% of the distance from the contour of the toner particle cross section to the center of gravity of the cross section is specified. Based on the toner cross section image in which the 10% boundary line is specified, the area (s1) occupied by the domain existing in the region within 10% of the distance from the contour of the toner particle cross section to the center of gravity of the cross section is measured in the cross section of the toner particle. The area of ​​the domain in a region within 10% of the distance between the outline of the cross section of the toner particle and the center of gravity of the cross section is calculated using the following formula.

[0202] That is, using the domain area S1 calculated above, the area of ​​the domain in the region within 10% of the distance between the contour and the center of gravity of the cross section of the toner particle is calculated as s1 / S1 x 100. This is performed for the cross sections of 100 toner particles, and the arithmetic mean value is regarded as the area of ​​the domain in the region within 10% of the distance between the contour and the center of gravity of the cross section.

[0203] The image processing software "ImageJ" is used for binarization and calculation of the number-average diameter.

[0204] <Method for measuring the primary average particle size based on the number of particles> The number-based primary average particle size of the fine particles is determined by measurement using the centrifugal sedimentation method. Specifically, 0.01 g of dried fine particles is placed in a 25 ml glass vial, and 0.2 g of 5% Triton solution and 19.8 g of RO water are added to prepare a solution. Next, the probe (the tip of the tip) of an ultrasonic disperser is immersed in the solution, and ultrasonic dispersion is performed for 15 minutes at an output of 20 W to obtain a dispersion. Next, using this dispersion, the number-average particle size of the primary particles is measured using a CPS Instruments DC24000 centrifugal sedimentation particle size distribution analyzer. The disk rotation speed is set to 18,000 rpm, and the true density is 1.3 g / cm. 3 Prior to measurement, the instrument is calibrated using polyvinyl chloride particles with an average particle size of 0.476 μm.

[0205] <Method of measuring weight-average particle size (D4) of toner (particles)> The weight average particle size (D4) of the toner (particles) is measured with an effective measurement channel count of 25,000 channels using a precision particle size distribution measuring device equipped with a 100 μm aperture tube and a fine hole electrical resistance method called "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.) and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) for setting measurement conditions and analyzing measurement data, and the weight average particle size (D4) is calculated by analyzing the measurement data.

[0206] The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter).

[0207] Before performing measurements and analysis, the dedicated software is set up as follows.

[0208] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement.

[0209] In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.

[0210] The specific measurement method is as follows. (1) Pour about 200 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Approximately 30 mL of the electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and approximately 0.3 mL of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7 consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water is added as a dispersant. (3) A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 mL of Conaminon N is added to this water tank. (4) Set the beaker (2) in the beaker fixing hole of the ultrasonic disperser, operate the ultrasonic disperser, and adjust the height of the beaker so that the resonance state of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner (particles) is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, add the electrolytic solution (5) in which the toner (particles) is dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4).

[0211] <Method for measuring the 50% particle size (D50) based on volume distribution of resin particles, wax particles, and colorant particles> The 50% particle size (D50) based on the volume distribution of each particle is measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.). Specifically, the measurement is performed according to the following procedure.

[0212] In order to prevent the measurement sample from clumping, the dispersion in which the measurement sample is dispersed is poured into an aqueous solution containing Family Fresh (manufactured by Kao Corporation) and stirred. After stirring, the measurement sample is poured into the above device and measured twice to obtain the average value.

[0213] The measurement conditions are as follows: measurement time is 30 seconds, the refractive index of the sample particles is 1.49, the dispersion medium is water, and the refractive index of the dispersion medium is 1.33.

[0214] The volumetric particle size distribution of the measurement sample is measured, and the particle size at which the cumulative volume from the small particle size side in the cumulative volume distribution is 50% from the measurement results is defined as the 50% particle size (D50) based on the volume distribution of each microparticle.

[0215] <Method of measuring resin softening point (Tm)> The softening point of the resin is measured using a constant load extrusion type capillary rheometer "Flow characteristic evaluation device Flow Tester CFT-500D" (Shimadzu Corporation) according to the manual that comes with the device. With this device, a constant load is applied from above the measurement sample by a piston while the measurement sample filled in a cylinder is heated and melted, and the molten measurement sample is extruded from the die at the bottom of the cylinder, and a flow curve showing the relationship between the piston descent amount and temperature can be obtained.

[0216] The softening point is the "melting temperature in the 1 / 2 method" described in the manual attached to the "Flow property evaluation device Flow Tester CFT-500D." The melting temperature in the 1 / 2 method is calculated as follows.

[0217] First, calculate half the difference between the amount of piston descent when the outflow ends (end of outflow, Smax) and the amount of piston descent when the outflow starts (minimum point, Smin) (this is X. X=(Smax-Smin) / 2). Then, the temperature of the flow curve when the amount of piston descent is the sum of X and Smin is the melting temperature in the 1 / 2 method.

[0218] The measurement sample is prepared by compressing approximately 1.0 g of resin at approximately 10 MPa for approximately 60 seconds using a tablet molding machine (e.g., NT-100H, manufactured by NPA Systems) in an environment of 25°C to form a cylindrical shape with a diameter of approximately 8 mm.

[0219] The specific operations for the measurement are performed according to the manual that comes with the device.

[0220] The measurement conditions for the CFT-500D are as follows. Test mode: Temperature rise method Starting temperature: 50℃ Achieved temperature: 200℃ Measurement interval: 1.0℃ Heating rate: 4.0℃ / min Piston cross-sectional area: 1.000cm 2 Test load (piston load): 10.0kgf (0.9807MPa) Preheat time: 300 seconds Die hole diameter: 1.0mm Die length: 1.0mm EXAMPLES

[0221] The basic configuration and features of the present invention have been described above, and the present invention will be specifically described below based on examples. However, the present invention is not limited to these. Note that parts are by weight unless otherwise specified.

[0222] <Production Example of Crystalline Resin 1> Solvent: toluene 100.0 parts Monomer composition 100.0 parts (The monomer composition is a mixture of behenyl acrylate, acrylonitrile, and styrene in the ratio shown below.) Behenyl acrylate (behenyl acrylate); the first polymerizable monomer (R 1 Carbon number 22): 60.00 parts Acrylonitrile (second polymerizable monomer): 16.00 parts Styrene (third polymerizable monomer): 24.00 parts Polymerization initiator: t-butyl peroxypivalate (NOF Corp.: Perbutyl PV): 0.5 parts The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. The reaction vessel was heated to 70°C while stirring at 200 rpm, and a polymerization reaction was carried out for 12 hours to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. Next, the temperature of the solution was lowered to 25°C, and then the solution was poured into 1000.0 parts of methanol while stirring, and the methanol insoluble matter was precipitated. The obtained methanol insoluble matter was filtered, washed with methanol, and then vacuum dried at 40°C for 24 hours to obtain crystalline resin 1, which is a first resin. The peak top temperature of the temperature-endothermic curve of crystalline resin 1 was 62°C.

[0223] <Production Examples of Crystalline Resin 2 to Crystalline Resin 13> The reaction was carried out in the same manner as in the production example of crystalline resin 1, except that the polymerizable monomers and the parts thereof were changed as shown in Table 1, to obtain crystalline resins 2 to 13, which are first resins.

[0224] [Table 1] The abbreviations in Table 1 are as follows. BEA: Behenyl acrylate OA: Octacosa acrylate MYA: Myricyl acrylate SA: Stearyl acrylate HA: Hexadecyl acrylate AN: Acrylonitrile MN: Methacrylonitrile AA: Acrylic acid St: styrene

[0225] <Production Example of Amorphous Resin 1> 50.0 parts of xylene was charged into an autoclave, and after replacing with nitrogen, the temperature was raised to 185°C while stirring and sealing. A mixed solution of 75.0 parts of styrene, 25.0 parts of n-butyl acrylate, and 1.0 part of di-tert-butyl peroxide and 20.0 parts of xylene was continuously added dropwise to the autoclave for 3 hours while controlling the temperature inside the autoclave at 185°C, and polymerization was carried out. The same temperature was maintained for another 1 hour to complete the polymerization, and the solvent was removed to obtain amorphous resin 1, which is a second resin. The SP value of amorphous resin 1 was 20.1 (J / cm 3 ) 0.5 The softening point (Tm) was 100°C.

[0226] <Production Example of Amorphous Resin 2> The following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane: 73.4 parts (0.19 moles) Terephthalic acid: 11.6 parts (0.07 moles) Adipic acid: 6.8 parts (0.05 moles) Titanium tetrabutoxide: 2.0 parts

[0227] Next, the atmosphere in the flask was replaced with nitrogen gas, and the temperature was gradually raised while stirring, and the mixture was stirred at a temperature of 200°C and reacted for 2 hours while distilling off the water produced. The pressure in the reaction vessel was then lowered to 8.3 kPa and maintained for 1 hour, after which it was cooled to 180°C and returned to atmospheric pressure (first reaction step).

[0228] Trimellitic anhydride: 8.2 parts (0.04 moles) tert-Butylcatechol (polymerization inhibitor): 0.1 parts The above materials were then added, the pressure in the reaction vessel was lowered to 8.3 kPa, and the reaction was carried out for 4 hours while maintaining the temperature at 150°C. The reaction was stopped by lowering the temperature (second reaction step), and a second resin, amorphous resin 2, was obtained. The SP value of amorphous resin 2 was 23.3 (J / cm 3 ) 0.5 The softening point (Tm) was 105°C.

[0229] <Production of toner particles by pulverization method> <Production Example of Toner Particle 1> ·Crystalline resin 1 50.0 parts Amorphous resin 1 50.0 parts 5.0 parts wax 1 (Fischer-Tropsch wax; maximum endothermic peak temperature 90℃) Colorant 1 9.0 parts (Cyan pigment made by Dainichi Seika: Pigment Blue 15:3) The above materials were mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 20 s -1 After mixing for 5 minutes, the mixture was kneaded at a discharge temperature of 120°C in a twin-screw kneader (PCM-30, Ikegai Corporation) set at a temperature of 110°C. The kneaded mixture was cooled and coarsely crushed to 1 mm or less in a hammer mill to obtain a coarsely crushed product. The coarsely crushed product was finely crushed in a mechanical crusher (T-250, Freund Turbo Corporation). Classification was then performed using a Faculty F-300 (Hosokawa Micron Corporation) to obtain toner particles 1. The classification operation conditions were a classification rotor rotation speed of 130 s -1 , Distributed rotor speed 120s -1 The weight average particle size (D4) of toner particles 1 was about 6.5 μm.

[0230] <Production of toner particles by emulsion aggregation method> <Production example of crystalline resin 1 fine particle dispersion> Toluene (Wako Pure Chemical Industries, Ltd.) 300 parts ·Crystalline resin 1 100 parts The above materials were weighed, mixed and melted at 100°C.

[0231] Separately, 5.0 parts of sodium dodecylbenzenesulfonate and 10.0 parts of sodium laurate were added to 700 parts of ion-exchanged water and dissolved by heating at 100°C. The toluene solution and the aqueous solution were then mixed and stirred at 7000 rpm using an ultra-high speed stirring device TK Robomix (manufactured by Primix). Furthermore, the mixture was emulsified at a pressure of 200 MPa using a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Kogyo). After that, the toluene was removed using an evaporator, and the concentration was adjusted with ion-exchanged water to obtain an aqueous dispersion (crystalline resin 1 fine particle dispersion) with a concentration of 20% by mass of crystalline resin 1 fine particles.

[0232] The 50% particle size (D50) based on volume distribution of the crystalline resin 1 was measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.40 μm (400 nm).

[0233] <Production Example of Crystalline Resin 2-13 Fine Particle Dispersion> In the manufacturing example of the microparticle dispersion of crystalline resin 1, except that the crystalline materials used were changed, manufacturing was performed in the same manner as in the manufacturing example of the microparticle dispersion of crystalline resin 1 to obtain microparticle dispersions of crystalline resins 2 to 13. The 50% particle diameter (D50) based on volume distribution of crystalline resins 2 to 13 was 0.40 μm, the same as that of crystalline resin 1.

[0234] <Production example of amorphous resin 1 fine particle dispersion> Tetrahydrofuran (Wako Pure Chemical Industries, Ltd.) 300 parts 100 parts of amorphous resin 1 Anionic surfactant Neogen RK (Daiichi Kogyo Seiyaku) 0.5 parts The above ingredients were weighed, mixed and dissolved.

[0235] Next, 20.0 parts of 1 mol / L ammonia water was added, and the mixture was stirred at 4000 rpm using an ultra-high speed stirring device TK Robomix (manufactured by Primix). Furthermore, 700 parts of ion-exchanged water was added at a rate of 8 g / min to precipitate amorphous resin 1 fine particles. Then, tetrahydrofuran was removed using an evaporator, and the concentration was adjusted with ion-exchanged water to obtain an aqueous dispersion (amorphous resin 1 fine particle dispersion) with a concentration of amorphous resin 1 fine particles of 20 mass%.

[0236] The volume distribution-based 50% particle size (D50) of the amorphous resin 1 fine particles was 0.14 μm (140 nm).

[0237] <Production example of amorphous resin 2 fine particle dispersion> In the manufacturing example of the amorphous resin 1 microparticle dispersion, except for changing the amorphous material used, the manufacturing was carried out in the same manner as in the manufacturing example of the amorphous resin 1 microparticle dispersion to obtain the amorphous resin 2 microparticle dispersion. The volume distribution standard 50% particle size (D50) of the amorphous resin 2 microparticles was 0.14 μm, the same as the amorphous resin 1 microparticles.

[0238] <Production Example of Wax Particle Dispersion> Wax 1 100.0 parts (Fischer-Tropsch wax; maximum endothermic peak temperature 90℃) Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 5 parts 395 parts of ion-exchanged water The above materials were weighed and placed in a mixing vessel equipped with a stirrer, then heated to 90°C and circulated through a Clearmix W Motion (M Technique) for 60 minutes to perform dispersion processing. The dispersion processing conditions were as follows: Rotor outer diameter: 3cm Clearance: 0.3mm Rotor speed: 19000 r / min Screen rotation speed: 19000 r / min

[0239] After the dispersion process, the mixture was cooled to 40°C under cooling process conditions of a rotor rotation speed of 1000 r / min, a screen rotation speed of 0 r / min, and a cooling rate of 10°C / min to obtain an aqueous dispersion (wax microparticle dispersion) with a wax microparticle concentration of 20% by mass.

[0240] The 50% particle size (D50) based on the volume distribution of the wax microparticles was measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.15 μm (150 nm).

[0241] <Production Example of Colorant Microparticle Dispersion> Colorant 1 50.0 parts (Cyan pigment made by Dainichi Seika: Pigment Blue 15:3) Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 7.5 parts 442.5 parts ion-exchanged water The above materials were weighed, mixed, dissolved, and dispersed for approximately 1 hour using a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd.) to obtain an aqueous dispersion (colorant microparticle dispersion) containing dispersed colorant with a concentration of 10% by mass of colorant microparticles.

[0242] The 50% particle size (D50) based on the volume distribution of the colorant fine particles was measured using a dynamic light scattering particle size distribution meter Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.20 μm (200 nm).

[0243] <Production Example of Toner Particle 2> ·Crystalline resin 1 fine particle dispersion 50.0 parts ·Amorphous resin 1 fine particle dispersion 50.0 parts Wax microparticle dispersion 5.0 parts Colorant fine particle dispersion 9.0 parts 20.0 parts ion-exchanged water The above materials were put into a round stainless steel flask and mixed. Then, a homogenizer Ultra Turrax T50 (IKA) was used to disperse the mixture at 5000 r / min for 10 minutes. After adding a 1.0% aqueous nitric acid solution and adjusting the pH to 3.0, the mixture was heated to 58°C in a heating water bath using a stirring blade while appropriately adjusting the rotation speed so that the mixture was stirred. The formed aggregated particles were appropriately confirmed using a Coulter Multisizer III, and the mixture was held until the weight average particle size (D4) reached about 6.4 μm. After that, a fine particle dispersion of crystalline resin 1 for post-treatment was added, and the mixture was held for another 30 minutes, after which the pH was adjusted to 9.0 using a 5% aqueous sodium hydroxide solution.

[0244] Thereafter, the mixture was heated to 75° C. while continuing to stir at 500 r / min, and then held at 75° C. for 1 hour to fuse the aggregated particles.

[0245] Thereafter, the resin was cooled to 50°C and held at that temperature for 3 hours to promote crystallization of the resin.

[0246] Thereafter, the mixture was cooled to 25° C., filtered and separated into solid and liquid, and then thoroughly washed with ion-exchanged water and dried to obtain toner particles 2. The weight average particle size (D4) of toner particles 2 was about 6.5 μm.

[0247] <Production Examples of Toner Particles 3 to 33> Toner particles 3 to 33 were obtained by carrying out the same production procedure as in the production example of toner particles 2, except that the materials and the rotation speed, temperature, and time in the fusing step were changed as shown in Table 2.

[0248] [Table 2]

[0249] The physical properties of the obtained toner particles 1 to 33 are summarized in Table 3.

[0250] [Table 3]

[0251] <Production example of fine particle 1> [Hydrolysis process] 43.2 g of RO water and 0.008 g of acetic acid as a catalyst were placed in a 200 ml beaker and stirred at 50° C. 27.2 g of tetraethoxysilane and 27.2 g of dimethyldimethoxysilane were added thereto and stirred for 1.5 hours to obtain a raw material solution.

[0252] [Polycondensation process] In a 1000 ml beaker, 68.8 g of RO water, 340.0 g of methanol, and 2.0 g of 25% ammonia water were added and stirred at 30° C. to prepare an alkaline aqueous medium. The raw material solution obtained in the hydrolysis step was added dropwise to this alkaline aqueous medium over a period of 1 minute. The mixture after the dropwise addition of the raw material solution was stirred for 1.5 hours while maintaining the temperature at 30° C. to allow the polycondensation reaction to proceed, and a polycondensation reaction liquid was obtained.

[0253] [Particle formation process] 1000g of RO water was placed in a 2000ml beaker, and the polycondensation reaction liquid obtained in the polycondensation step was added dropwise over 10 minutes while stirring at 30°C. As soon as the polycondensation reaction liquid was mixed with the water, it became cloudy, and a dispersion containing fine particles was obtained.

[0254] [Hydrophobization process] 27.1 g of hexamethyldisilazane was added as a hydrophobizing agent to the dispersion containing the silicon polymer particles having siloxane bonds obtained in the particulation step, and the mixture was stirred at 60°C for 2.5 hours. The powder that precipitated at the bottom of the solution after standing for 5 minutes was collected by suction filtration and dried under reduced pressure at 120°C for 24 hours to obtain microparticles 1. The number average particle size of the primary particles of the obtained microparticles 1 was 0.10 μm (100 nm). The physical properties of the obtained microparticles 1 are shown in Table 4.

[0255] <Production Example of Microparticle 2> Except for changing the stirring temperature in the hydrolysis step to 55° C. and changing the amount of 25% ammonia water used in the polycondensation step to 1.8 g, the same procedure as in the production example of microparticles 1 was followed to obtain microparticles 2. The physical properties of the obtained microparticles 2 are shown in Table 4.

[0256] <Production example of fine particles 3> Except for changing the amount of 25% ammonia water used in the condensation polymerization step to 1.8 g, the same procedure as in the production example of microparticles 1 was followed to obtain microparticles 3. The physical properties of the obtained microparticles 3 are shown in Table 4.

[0257] <Production Example of Microparticle 4> Except for changing the stirring temperature in the hydrolysis step to 60° C. and changing the amount of 25% ammonia water used in the polycondensation step to 1.5 g, the same procedure as in the production example of microparticles 1 was followed to obtain microparticles 4. The physical properties of the obtained microparticles 4 are shown in Table 4.

[0258] <Production Example of Microparticle 5> Except for changing the stirring temperature in the hydrolysis step to 55° C. and changing the amount of 25% ammonia water used in the polycondensation step to 2.2 g, the same procedure as in the production example of microparticles 1 was followed to obtain microparticles 5. The physical properties of the obtained microparticles 5 are shown in Table 4.

[0259] <Production Example of Microparticle 6> Except for changing the stirring temperature in the hydrolysis step to 45° C. and changing the amount of 25% ammonia water used in the polycondensation step to 2.4 g, the same procedure as in the production example of microparticles 1 was followed to obtain microparticles 6. The physical properties of the obtained microparticles 6 are shown in Table 4.

[0260] <Production Example of Microparticle 7> Except for changing the stirring temperature in the hydrolysis step to 65° C. and changing the amount of 25% ammonia water used in the polycondensation step to 1.5 g, the same procedure as in the production example of microparticles 1 was followed to obtain microparticles 7. The physical properties of the obtained microparticles 7 are shown in Table 4.

[0261] <Production Examples of Fine Particles 8 to 13> Microparticles 8 to 13 were obtained by carrying out the same production procedure as in the production example of microparticles 7, except that the materials were changed to those shown in Table 4. The physical properties of the obtained microparticles 8 to 13 are shown in Table 4.

[0262] <Production Example of Microparticle 14> In a 2000 ml beaker, 124.0 g of ethanol, 24.0 g of RO water, and 10.0 g of 28% aqueous ammonia were added, and the temperature of the solution was adjusted to 70° C., and 232.0 g of tetraethoxysilane and 84.0 g of 5.4% aqueous ammonia were added dropwise over 0.5 hours while stirring. After the addition was completed, stirring was continued for another 0.5 hours to carry out hydrolysis, thereby obtaining a dispersion of fine particles 14.

[0263] To the dispersion obtained in the above step, 95.0 g of hexamethyldisilazane was added at room temperature, and then the dispersion was heated to 50-60°C and stirred for 3.0 hours, and the powder in the dispersion was collected by suction filtration and dried under reduced pressure at 120°C for 24 hours to obtain microparticles 14. The physical properties of the obtained microparticles 14 are shown in Table 4.

[0264] <Production example of fine particles 15> A double-tube hydrocarbon-oxygen mixed burner capable of forming an inner flame and an outer flame was used as the combustion furnace. A two-fluid nozzle for injecting slurry was installed in the center of the burner, and the raw material silicon compound (silicon tetrachloride) was introduced. Combustible hydrocarbon-oxygen gas was injected from around the two-fluid nozzle, forming the inner and outer flames, which are reducing atmospheres.

[0265] The amount and flow rate of the combustible gas and oxygen were controlled to adjust the atmosphere, temperature, flame length, etc. Fine particles were formed from the silicon compound in the flame, and were fused until they reached the desired particle size. After cooling, the particles were collected using a bag filter or the like to obtain fine particles 15.

[0266] The physical properties of the obtained microparticles 15 are shown in Table 4.

[0267] [Table 4] Monomer species Q: Tetraethoxysilane T: Trimethoxymethylsilane D: Dimethyldimethoxysilane M: Trimethylsilane

[0268] <Production Example of Toner 1 (Example 1)> 100 parts of toner particles ·Fine particles 1 5.0 parts The above materials were mixed in a Henschel mixer FM-10C (Mitsui Miike Chemical Industry Co., Ltd.) at a rotation speed of 30 s -1 The mixture was mixed at 10 minutes rotation time to obtain toner 1.

[0269] <Production Examples of Toners 2 to 53 (Examples 2 to 47, Comparative Examples 1 to 6)> Toners 2 to 53 were obtained by carrying out the same production procedure as in the production example of toner 1, except that the materials were changed to those shown in Table 5.

[0270] [Table 5]

[0271] <Magnetic Carrier 1 Manufacturing Example> Number average particle size: 0.30μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 1 Number average particle size: 0.50μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 2 To 100 parts of each of the above materials, 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added, and the mixture was mixed and stirred at high speed in a container at 100° C. or higher to treat each of the fine particles.

[0272] Phenol: 10% by weight Formaldehyde solution: 6% by weight (40% by weight of formaldehyde, 10% by weight of methanol, 50% by weight of water) Magnetite treated with the above silane compound 1:58 mass% Magnetite treated with the above silane compound 2: 26% by mass 100 parts of the above material, 5 parts of 28% by mass aqueous ammonia, and 20 parts of water were placed in a flask, and the temperature was raised to 85°C in 30 minutes and maintained at 85°C while stirring and mixing, and a polymerization reaction was carried out for 3 hours to harden the resulting phenolic resin. The hardened phenolic resin was then cooled to 30°C, and water was added, after which the supernatant liquid was removed, and the precipitate was washed with water and then air-dried. This was then dried at a temperature of 60°C under reduced pressure (5 mmHg or less) to obtain a spherical magnetic carrier 1 with magnetic material dispersion. The 50% particle diameter (D50) based on volume was 34.2 μm.

[0273] <Production Examples of Two-Component Developers 1 to 53> Toners 1 to 53 and magnetic carrier 1 were mixed in a V-type mixer (V-10 type: Tokuju Seisakusho Co., Ltd.) for 0.5 s to obtain a toner concentration of 9% by mass. -1 The mixture was mixed for 5 minutes to obtain two-component developers 1 to 53.

[0274] <Toner Evaluation> The image forming apparatus used was a modified Canon imagePRESS C800 full-color copier equipped with an intermediate transfer belt, and two-component developer 1 was placed in the cyan station developer. The modifications to the apparatus included the fixing temperature, process speed, and DC voltage V of the developer carrier. DC , the charging voltage of the electrostatic latent image carrier V D The laser power and the laser power can be freely set. The image output evaluation is performed by outputting a FFh image (solid image) with the desired image ratio, and adjusting the V so that the amount of toner on the FFh image on the paper is as desired. DC , V D and laser power were adjusted and the evaluation described below was performed.

[0275] FFh is a hexadecimal value representing 256 gradations, with 00h being the first gradation (white background) of the 256 gradations, and FFh being the 256th gradation (solid area) of the 256 gradations.

[0276] The evaluation was performed based on the following evaluation methods, and the results are shown in Table 6.

[0277] [Low temperature fixability] Paper: Mondi color copy paper (300.0 g / m 2 ) (Sold by mondi) Toner load on paper: 1.00mg / cm 2 (FFh image) (Adjusted by DC voltage VDC of developer carrier, charging voltage VD of electrostatic latent image carrier, and laser power) Evaluation image: A 2cm x 5cm image placed in the center of the A4 paper. Test environment: Low temperature and low humidity environment: Temperature 15℃ / Humidity 10%RH (hereinafter referred to as "L / L") Fixing temperature: 170℃ Process speed: 348mm / sec

[0278] The above evaluation image was output, and the low-temperature fixability was evaluated. The value of the image density reduction rate was used as an evaluation index for the low-temperature fixability. The image density reduction rate was measured using an X-Rite color reflection densitometer (500 series: manufactured by X-Rite Corporation) by first measuring the image density at the center. Next, the part where the image density was measured was subjected to pressure of 4.9 kPa (50 g / cm 2 The fixed image was rubbed (five times back and forth) with Silbon paper under a load of 1000 g / m2, and the image density was measured again. The rate of decrease in image density before and after rubbing was calculated using the following formula. The resulting rate of decrease in image density was evaluated according to the following evaluation criteria. If the evaluation was A to F, it was judged to be good. Image density reduction rate = (Image density before rubbing - Image density after rubbing) / (Image density before rubbing) x 100

[0279] (Evaluation Criteria) A: Image density reduction rate is less than 0.5% B: Image density reduction rate: 0.5% or more and less than 1.0% C: Image density reduction rate: 1.0% or more and less than 2.0% D: Image density reduction rate: 2.0% or more and less than 3.0% E: Image density reduction rate: 3.0% or more and less than 4.0% F: Image density reduction rate: 4.0% or more and less than 5.0% G: Image density reduction rate: 5.0% to less than 6.0% H: Image density reduction rate 6.0% or more

[0280] [Emboss transferability] Paper: Lezac 66 (302.0 g / m 2 ) (Embossed paper, sold by Tokai Tokushu Paper Co., Ltd.) Toner load on paper: 0.70mg / cm 2 (FFh image) (Mondi color copy paper (250.0 g / m 2 ) (sold by Mondi) to check the amount of toner on the paper in advance, and the DC voltage V DC , the charging voltage of the electrostatic latent image carrier V D , and adjusted by laser power) Evaluation image: Image placed on the entire A4 surface of Lezac 66 Fixing test environment: Normal temperature and humidity environment (temperature 23°C / humidity 50% RH (hereinafter N / N)) Fixing temperature: 180℃ Process speed: 173mm / sec

[0281] The evaluation image was output and the emboss transferability was evaluated. The standard deviation of brightness was used as an evaluation index for the emboss transferability. The image was read using a scanner (product name: CanoScan 9000F, manufactured by Canon Inc.) with a reading resolution of 1200 dpi and image correction processing OFF, and trimmed to a range of 2,550 x 2,550 pixels (approximately 10.8 x 10.8 cm). Next, a brightness value histogram (vertical axis: frequency (number of pixels), horizontal axis: brightness, brightness value is expressed in the range of 0 to 255) of the image data described above was obtained. In addition, the brightness standard deviation of the image data was calculated based on the obtained brightness value histogram. If the evaluation was A to P, it was judged to be good. The brightness standard deviation was calculated using the image processing software "ImageJ".

[0282] (Evaluation criteria: luminance standard deviation) A: Less than 2.0 B: 2.0 or more and less than 4.0 C: 4.0 or more and less than 6.0 D: 6.0 or more and less than 8.0 E: 8.0 or more and less than 10.0 F: 10.0 or more and less than 12.0 G: 12.0 or more and less than 14.0 H: 14.0 or more and less than 16.0 I: 16.0 or more and less than 18.0 J: 18.0 or more and less than 20.0 K: 20.0 or more and less than 22.0 L: 22.0 or more and less than 24.0 M: 24.0 or more and less than 26.0 N: 26.0 or more and less than 28.0 O: 28.0 or more and less than 30.0 P: 30.0 or more and less than 32.0 Q: 32.0 or more and less than 34.0 R: 34.0 or more and less than 36.0 S: 36.0 or more and less than 38.0 T:38.0 or more

[0283] Two-component developers 2 to 53 were also evaluated in the same manner as two-component developer 1. The results are shown in Table 6.

[0284] [Table 6]

Claims

1. A toner particle containing a binder resin having a first resin and a second resin, and a toner having fine particles on the surface of the toner particle, the first resin is a crystalline resin and the second resin is an amorphous resin; a cross section of the toner observed by a transmission electron microscope has a matrix domain structure composed of a matrix containing the first resin and a domain containing the second resin, and the ratio of the first resin to the total area of ​​the matrix and the domain combined is 35 area % or more and 70 area % or less; The first resin has a first monomer unit represented by the following formula (1): 【Chemistry 1】 [In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms. a ratio of the first monomer unit to the total mass of all monomer units of the crystalline resin is 40.0 mass% or more and 80.0 mass% or less; The microparticles are silicon-containing microparticles, 29 The toner is characterized in that, in a chart obtained by Si-NMR measurement, when the total peak area derived from the silicon-containing fine particles is A and the area derived from Si-OH is B, the following formula (2) is satisfied: B / A≧1.0%...(2)

2. 2. The toner according to claim 1, wherein, upon cross-sectional observation of the toner particle, the domain portion has a number-average equivalent circle diameter of 20 nm to 500 nm.

3. 3. The toner according to claim 1, wherein, in a cross section of the toner particle observed with a transmission electron microscope, an area of ​​the domain in a region within 10% of a distance between the contour of the cross section of the toner particle and the center of gravity of the cross section accounts for 10% to 30% of a total area occupied by the domain.

4. The microparticles are silicon-containing microparticles, 29 In the chart obtained by Si-NMR measurement, the total peak area derived from the fine particles is represented as A, Si-R 2 (R 2 The toner according to any one of claims 1 to 3, wherein when an area derived from the group consisting of the alkyl groups (a, b, c) and the alkyl groups (b) is defined as C, the following formula (3) is satisfied: 20.0%≦C / A≦45.0% (3)

5. The microparticles are silicon-containing microparticles, 29 In the chart obtained by Si-NMR measurement, the total peak area derived from the fine particles is represented as A, Si-R 2 (R 2 The toner according to any one of claims 1 to 4, wherein when an area derived from the group consisting of the alkyl group and the aryl group (R represents an alkyl group) is defined as C, the following formula (4) is satisfied: 26.0%≦C / A≦45.0% (4)

6. 6. The toner according to claim 1, wherein the fine particles have a number-based average primary particle diameter of 20 nm or more and 300 nm or less.

7. 7. The toner according to claim 1, wherein the content of the fine particles is from 0.1 parts by mass to 20.0 parts by mass based on 100 parts by mass of the toner particles.

Citation Information

Patent Citations

  • Amorphous silica particle

    JP2012227448A

  • toner

    JP2013047754A

  • Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method

    JP2013097321A

  • Toner, developer, and image forming device

    JP2014059489A

  • Toner

    JP2014130243A